An ortho‐Quinone Methide Mediates Disulfide Migration in the Biosynthesis of Epidithiodiketopiperazines - Fan, Jie; Ran, Huomiao; Wei, Peng‐Lin; Li, Yuanyuan; Liu, Huan; Li, Shu‐Ming; Yin, Wen‐Bing (Angewandte Chemie International Edition, 2023)
The transannular disulfide functions as a key structural element imparting diverse biological activities to epidithiodiketopiperazines (ETPs). Although mechanisms were proposed in previous studies, α,β′‐disulfide formation in ETPs is not well‐determined owing to the failure to identify the hypothetical intermediate. Herein, we characterize the key ortho‐quinone methide (o‐QM) intermediate and prove its involvement in the carbon‐sulfur migration from an α,α′‐ to an α,β′‐disulfide by elucidating pretrichodermamide A biosynthesis, which is catalyzed by a FAD‐dependent thioredoxin oxygenase TdaE harboring a noncanonical CXXQ motif. Biochemical investigations of recombinant TdaE and mutants demonstrated that the construction of the α,β′‐disulfide was initiated by Gln140 triggering proton ion for generation of the essential o‐QM intermediate, accompanied by β′‐acetoxy elimination. Subsequent attack on the α,α′‐disulfide by Cys137 led to disulfide migration and spirofuran formation. This study expands the biocatalytic toolbox for transannular disulfide formation and sets the stage for the targeted discovery of bioactive ETPs. The formation of the α,β′‐disulfide in pretrichodermamide A involves the formation of an α,α′‐disulfide by the oxygenase TdaR containing the canonical CXXC motif, followed by disulfide migration by the oxygenase TdaE containing a specialized CXXQ motif, via an ortho‐quinone methide intermediate. The enzymatic cascade reactions can be considered as a general catalytic mechanism for α,β′‐disulfide formation in epidithiodiketopiperazines (ETPs).